PENGARUH PENDAPATAN SENDIRI, JENIS PEMERINTAH DAERAH DAN LETAK PEMERINTAH DAERAH TERHADAP PERILAKU OPORTUNISTIK LEGISLATIF DI DEWAN PERWAKILAN RAKYAT KABUPATEN ACEH UTARA - Murhaban Murhaban; Aris Munandar (Jurnal Akuntansi dan Keuangan, 2019)
The purpose of this study was to learn to find out their own income, types of regional government and regional government related to opportunistic legislatures in the North Aceh District People's Representative Council (DPRK). The sample in this study amounted to 45 respondents taken from 45 members of the North Aceh District Representative Council. Data obtained by collecting questionnaires. The data analysis technique used is a simple linear regression analysis technique. The results of the study indicate their own expenditure on legislative opportunistic policies in North Aceh District. From the results of the research conducted with the facts issued regarding the contribution to the opportunistic legislature because of this, the income itself is related to the importance of development in development in North Aceh District. The type of regional government towards legislative opportunistic behavior has a positive and significant influence. The results of the study indicate that there are differences between the types of regional government which will facilitate the government in carrying out the duties of the board members who regulate the budget allocation process in each development as expected. Regional laws related to legislative opportunistic behavior have a positive and significant relationship. The results of the study indicate that there is a regularity of regional government that will make it easier for the government to supervise legislative opportunists that are as expected. The calculated F value is 12,534 with a significance level of 0,000. While Ftable with a confidence level of 95% (α = 5%) on the probability of 0.05 and df2 = n-k-1 (45-4 = 41) and obtained the value of Ftable of 3.998. Then the F-test results show that Fcount> Ftable (12,534> 4,078).